Understanding decision making in security operations centres: building the case for cyber deception technology - Reeves, Andrew; Ashenden, Debi (Frontiers in Psychology, 2023)
A Security Operations Centre (SOC) is a command centre where analysts monitor network activity, analyse alerts, investigate potential threats, and respond to incidents. By analysing data activities around the clock, SOC teams are crucial in ensuring the prompt detection and response to security incidents. SOC analysts work under considerable pressure to triage and respond to alerts in very short time frames. Cyber deception technology offers the promise of buying SOC analysts more time to respond by wasting the resources and time of attackers, yet such technology remains underutilised. We carried out a series of interviews with experts to uncover the barriers which prevent the effective implementation of cyber deception in SOCs. By using thematic analysis on the data, it was clear that while cyber deception technology is promising it is hindered by a lack of use cases, limited empirical research that demonstrates the efficacy of the technology, hesitancy to embrace a more active form of cyber defence, issues surrounding the over promising of results by off-the-shelf vendors, and an aversion to interrupting the decision-making processes of SOC analysts. Taking this last point about the decision-making processes of SOC analysts we make the case that naturalistic decision making (NDM) would help us better understand how SOC analysts make decisions and how cyber deception technology could be used to best effect.